Impulse oscillometry: reference values in children 100 to 150 cm in height and 3 to 10 years of age - Frei, Jennifer; Jutla, Jagtar; Kramer, Gretchen; Hatzakis, George E; Ducharme, Francine M; Davis, G Michael (Chest, 2005)
To generate reference equations in North American children to be used for assessing respiratory function through the forced oscillation (Rfo) technique, and to determine the changes in oscillatory resistance, reactance, and resonant frequency (Fres) in relation to age, body height, and weight. A prospective cross-sectional study performed on healthy children selected according to strict criteria of American Thoracic Society and European Respiratory Society recommendations. Triplicate measures were obtained of resistance and reactance at 5, 10, 15, 20, 25, and 35 Hz as well as Fres through the impulse oscillometer (MasterScreen IOS; Jaeger/Toennies; Höchberg, Germany). Two hundred twenty-two white children--normally distributed within the 3- to 10-year age range and 100 to 150 cm in height--were recruited in Montreal, Canada. We used regression analysis to generate multiple predictive equations separately per gender and frequency on age, height, and body weight. Stepwise multiple regression in both natural and logarithmic forms for height, weight, age, and gender showed that standing height was the only significant predictor for all variables. Minimal variability was noted in each subject among the triplicate measurements (p = 0.68 to 0.96). Coherence was > 0.9 at all oscillating frequencies except 5 Hz (< 0.72), with tendencies to lower values in young children. Resistance and Fres decrease by height, but also by age; and reactance increases. As opposed to our past experience with spirometry in compatible age groups, the Rfo technique was well accepted by preschool children.